A water-based paint for a cement floor and a method for preparing the same
Patent Information
- Application Number
- CN202411632335.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-11-15
AI Technical Summary
虽然可以通过增加交联密度来提高硬度,但往往会导致涂层变脆,实际应用效果不理想
[0053]1.优异的界面性能:涂层与水泥基材的附着力达到0级,且耐水浸泡后性能保持稳定;
Smart Images

Figure BDA0005136244600000151 
Figure BDA0005136244600000152
Abstract
Description
Technical Field
[0001] This invention relates to the field of water-based coatings technology, and in particular to a water-based coating suitable for cement floors and its preparation method. Background Technology
[0002] Cement floors, as one of the most common substrates in industrial and civil buildings, have always been a key focus of the coatings industry for surface protection. While traditional solvent-based epoxy resin coatings offer excellent abrasion resistance and adhesion, their high volatile organic compound (VOC) content poses serious threats to the environment and human health. In response to environmental protection requirements, water-based coatings have gradually become a research hotspot. However, existing water-based coatings still face numerous technical challenges in their application to cement floors:
[0003] First, due to the high alkalinity and porous nature of cement-based substrates, traditional water-based coatings exhibit poor interfacial bonding with the substrate, easily leading to problems such as blistering and peeling. Although adding coupling agents can improve interfacial bonding, a single chemical bonding method is insufficient to cope with complex service environments.
[0004] Secondly, the film-forming process of water-based coatings is significantly affected by environmental conditions, especially in low-temperature or high-humidity environments, where defects such as incomplete film formation and cracking are prone to occur. Existing technologies improve this problem by adding film-forming aids, but this often affects the final performance of the coating.
[0005] Furthermore, the mechanical properties of water-based coatings, especially abrasion resistance and toughness, still lag significantly behind those of solvent-based coatings. Although hardness can be increased by increasing crosslinking density, this often leads to brittle coatings and unsatisfactory practical application results.
[0006] Furthermore, existing water-based coatings exhibit poor water resistance, which is directly related to the presence of their hydrophilic components. Although water resistance can be improved through hydrophobic modification, this often affects the stability and application performance of the coating.
[0007] Finally, traditional water-based coatings have poor storage stability, and the fillers are prone to sedimentation, requiring frequent stirring, which brings many inconveniences to practical applications. Summary of the Invention
[0008] To address the above problems, this invention proposes an innovative water-based coating formulation suitable for cement floors and its preparation method.
[0009] The purpose of this invention is to provide a water-based coating suitable for cement floors, wherein the water-based coating comprises the following components by weight:
[0010] 60-80 parts acrylic emulsion
[0011] 3-5 parts of N-hydroxyethylacrylamide
[0012] 2-4 parts of modified nano-silica
[0013] 0.1-0.3 parts of graphene oxide,
[0014] 1-2 parts of polyethylene glycol methyl ether methacrylate
[0015] 2-4 parts of ethyl 2-(dimethylamino)methacrylate
[0016] Defoamer 0.2-0.6 parts,
[0017] Leveling agent 0.5-1 part,
[0018] Wetting agent 0.3-0.6 parts,
[0019] 4-10 parts of film-forming aid,
[0020] Thickener 0.5-1.5 parts,
[0021] 0.1-0.2 parts of anti-mold and bactericide.
[0022] 20-40 parts of filler.
[0023] Specifically, the acrylic emulsion includes a pure acrylic emulsion and an aqueous acrylic emulsion, wherein the weight ratio of the pure acrylic emulsion to the aqueous acrylic emulsion is 4:1; wherein the pure acrylic emulsion is a styrene-acrylic emulsion, and the aqueous acrylic emulsion is selected from a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate.
[0024] Specifically, the modified nano-silica is nano-silica modified with (3-glycidylpropoxy)trimethoxysilane, and the particle size of the nano-silica is 20-30 nm.
[0025] Specifically, the thickener is quaternary ammonium salt modified hydroxyethyl cellulose, the antifungal and bactericidal agent includes a mixture of 2-methyl-4-isothiazolin-3-one and 1,2-benzisothiazol-3(2H)-one in a weight ratio of 1:2, and the filler includes modified calcium carbonate, nano zinc oxide and hollow glass microspheres in a weight ratio of 3:1:1.
[0026] Specifically, the polyethylene glycol segment in the polyethylene glycol methyl ether methacrylate has 45-50 repeating units, the defoamer is an organosilicon quaternary ammonium salt, the leveling agent is polydimethylsiloxane, and the wetting agent is polyoxyethylene ether.
[0027] Specifically, the film-forming aid is selected from a mixture of dodecyl alcohol ester and propylene glycol methyl ether, wherein the weight ratio of dodecyl alcohol ester and propylene glycol methyl ether is 1:1.
[0028] A method for preparing the water-based coating includes the following steps:
[0029] (1) Preparation of modified nano-silica:
[0030] Nano-silica was vacuum dried at 105℃ for 4 hours;
[0031] Prepare an ethanol / water mixed solution, wherein the volume ratio of ethanol to water is 8:2;
[0032] Add (3-glycidylpropoxy)trimethoxysilane to the mixture and adjust the pH to 4-5;
[0033] Pre-hydrolysis was performed by stirring at room temperature for 30 minutes.
[0034] The pretreated nano-silica was dispersed in ethanol and ultrasonically dispersed for 15 min.
[0035] Slowly add the pre-hydrolyzed silane coupling agent solution, heat to 60℃, and stir the reaction for 4 hours;
[0036] Centrifuge, wash three times with ethanol, vacuum dry at 60℃ for 12 hours, and grind through a 200-mesh sieve;
[0037] (2) Preparation of water-based coatings:
[0038] Mix the acrylic emulsion with N-hydroxyethylacrylamide at a stirring speed of 400-600 r / min;
[0039] Add the modified nano-silica and graphene oxide obtained in step (1) and ultrasonically disperse for 15-20 min;
[0040] Add polyethylene glycol methyl ether methacrylate and ethyl 2-(dimethylamino)methacrylate sequentially, and control the temperature at 45-50℃.
[0041] Add the thickener and filler in sequence, and stir for 3 minutes;
[0042] Add the defoamer, film-forming aid, and leveling agent dropwise at a rate of 0.5-1 g / min, and continue stirring for 30 min.
[0043] Specifically, in step (2), nitrogen protection is used when adding polyethylene glycol methyl ether methacrylate and ethyl 2-(dimethylamino)methacrylate.
[0044] Specifically, in step (2), when adding modified nano-silica and graphene oxide, the dispersion temperature is controlled at 30-35℃.
[0045] Specifically, the modified calcium carbonate is stearic acid-modified ultrafine calcium carbonate with a particle size of 0.7-1.2 μm; the nano zinc oxide has a particle size of 30-50 nm; and the hollow glass microspheres have a particle size of 40-60 μm and a density of 0.21-0.25 g / cm³. 3 .
[0046] The purpose of this invention is to address the aforementioned technical problems by developing a novel waterborne coating system. This system achieves excellent overall performance through molecular design and the synergistic effect of multiple components.
[0047] First, a semi-interpenetrating network structure was constructed at the molecular level by introducing N-hydroxyethylacrylamide with active double bonds. This component can not only copolymerize with acrylates, but its hydroxyl and amide groups can also form multiple hydrogen bonds with cementitious substrates, significantly improving interfacial bonding.
[0048] Secondly, a special nanocomposite system is employed, including silica and graphene oxide modified with (3-glycidoxy)trimethoxysilane. This composite filler not only provides a multi-scale reinforcing effect but also forms a unique physical cross-linking network, significantly improving the overall mechanical properties of the coating.
[0049] Of particular note is that this invention is the first to introduce the pH-responsive component ethyl 2-(dimethylamino)methacrylate into a cement floor coating system. This component promotes emulsion particle deformation in the alkaline environment during the initial construction phase, and gradually increases crosslinking density as the pH decreases during cement hydration, thus achieving dynamic performance control.
[0050] In terms of interface engineering, this invention uses polyethylene glycol methyl ether methacrylate as an amphiphilic modifier. Its unique molecular structure forms an ordered arrangement at the interface, which not only improves the compatibility of the system, but also provides additional physical crosslinking points.
[0051] Furthermore, the storage stability issue was successfully resolved through the synergistic effect of quaternary ammonium salt-modified hydroxyethyl cellulose and a multi-level filler system. The modified thickener provides sufficient viscosity to prevent sedimentation under low shear and exhibits shear-thinning behavior under high shear, ensuring good workability.
[0052] Compared with the prior art, the water-based coating for cement floors and its preparation method of the present invention can achieve the following beneficial effects:
[0053] 1. Excellent interface performance: The coating has a zero adhesion to the cement substrate and its performance remains stable after water immersion.
[0054] 2. Superior mechanical properties: Abrasion resistance is more than 3 times higher than traditional water-based coatings, while maintaining good toughness;
[0055] 3. Outstanding adaptability: Ideal film formation can be achieved in the temperature range of 5-40℃, and it is not sensitive to the moisture content of the substrate;
[0056] 4. Excellent durability: No significant performance degradation after 2000 hours of weathering test, with significantly improved alkali resistance and water resistance;
[0057] 5. Excellent processability: It has a storage stability of over 12 months, is easy to construct, and is environmentally friendly.
[0058] The achievement of these properties is attributed to the innovations of this invention in molecular design, interface regulation, and process optimization, providing a new technical solution for the development of cement floor coatings. Detailed Implementation
[0059] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0060] Example 1
[0061] A water-based coating suitable for cement floors and its preparation method
[0062] The water-based coating of this embodiment is formulated from the following components in parts by weight:
[0063] The acrylic emulsion selected is 60 parts, which includes a pure acrylic emulsion and an aqueous acrylic emulsion mixed at a weight ratio of 4:1. The pure acrylic emulsion is a styrene-acrylic emulsion, and the aqueous acrylic emulsion is a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate.
[0064] Furthermore, 3 parts of N-hydroxyethyl acrylamide are selected, wherein the content of active double bonds is not less than 98%; 2 parts of modified nano-silica are selected; 0.1 parts of graphene oxide are selected, with a sheet thickness of 0.8-1.2 nm; 1 part of polyethylene glycol methyl ether methacrylate is selected, wherein the number of repeating units of polyethylene glycol segments is 45; and 2 parts of 2-(dimethylamino)methacrylate are selected, with a purity ≥99%.
[0065] Preferably, the defoamer is selected from 0.2 parts of organosilicon quaternary ammonium salt; the leveling agent is selected from 0.5 parts of polydimethylsiloxane; the wetting agent is selected from 0.3 parts of polyoxyethylene ether; and the film-forming aid is selected from 4 parts of a 1:1 mixture of dodecyl alcohol ester and propylene glycol methyl ether.
[0066] Specifically, the thickener is 0.5 parts of quaternary ammonium salt modified hydroxyethyl cellulose with a modification degree of 0.35-0.45; the antifungal and bactericidal agent is 0.1 parts of a 1:2 mixture of 2-methyl-4-isothiazolin-3-one and 1,2-benzisothiazol-3(2H)-one; the filler is stearic acid modified ultrafine calcium carbonate (particle size 0.7 μm), nano zinc oxide (particle size 30 nm), and hollow glass microspheres (particle size 40 μm, density 0.21 g / cm³). 3 Mix 20 portions in a 3:1:1 weight ratio.
[0067] The preparation method includes the following steps:
[0068] First, modified nano-nitrate dioxide was prepared. The specific steps are as follows: 20nm nano-silica is vacuum dried at 105℃ for 4 hours to fully remove surface adsorbed water; then, a mixed solution of ethanol and water in a volume ratio of 8:2 is prepared, ensuring adequate hydrolysis of the silane coupling agent; (3-glycidylpropoxy)trimethoxysilane is added to this mixed solution, and the pH is adjusted to 4 with glacial acetic acid. This pH value is conducive to the hydrolysis of silane groups without causing excessive condensation; pre-hydrolysis is carried out by stirring at room temperature for 30 minutes to ensure complete hydrolysis of the silane coupling agent; the pretreated nano-silica is dispersed in ethanol and ultrasonically dispersed for 15 minutes to form a stable suspension; then, the pre-hydrolyzed silane coupling agent solution is slowly added dropwise at a rate of 2mL / min, the temperature is raised to 60℃, and the reaction is stirred for 4 hours. Under these conditions, the surface silanol groups and the silane coupling agent can fully react; finally, the mixture is centrifuged at 8000rpm, washed three times with ethanol to remove unreacted substances, vacuum dried at 60℃ for 12 hours, and ground through a 200-mesh sieve.
[0069] Secondly, the water-based coating was prepared. The specific process is as follows: Acrylic emulsion and N-hydroxyethyl acrylamide were mixed at a stirring speed of 400 r / min, which ensures thorough mixing of the components without introducing excessive air bubbles; the modified nano-silica and graphene oxide prepared above were added, and ultrasonically dispersed at 30℃ for 15 min. This temperature and time ensures uniform dispersion of the nanofiller without affecting the stability of the emulsion; under nitrogen protection, polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)methacrylate ethyl ester were added sequentially, with the temperature controlled at 45℃. Nitrogen protection prevents free radical-initiated prepolymerization; then, thickener and filler were added sequentially, and stirred for 3 min until homogeneous; finally, a mixture of defoamer, film-forming aid, and leveling agent was added dropwise at a rate of 0.5 g / min, and stirring was continued for 30 min to obtain the finished product.
[0070] In this embodiment, by rationally controlling the proportions of each component and the preparation process parameters, especially through the optimization of the surface modification and dispersion process of nano-silica, the final product exhibits excellent substrate wettability and adhesion. Specifically, quaternary ammonium salt-modified hydroxyethyl cellulose, acting as a thickener, provides sufficient viscosity under low shear conditions to prevent filler sedimentation, while rapidly reducing viscosity during high shear application, ensuring good workability.
[0071] Example 2
[0072] A water-based coating suitable for cement floors and its preparation method
[0073] The water-based coating of this embodiment is formulated from the following components in parts by weight:
[0074] The acrylic emulsion is selected in 70 parts, which includes a pure acrylic emulsion and an aqueous acrylic emulsion mixed in a weight ratio of 4:1. The pure acrylic emulsion is a styrene-acrylic emulsion, and the aqueous acrylic emulsion is a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate.
[0075] Furthermore, 4 parts of N-hydroxyethyl acrylamide are selected, with an active double bond content of not less than 98%; 3 parts of modified nano-silica are selected; 0.2 parts of graphene oxide are selected, with a sheet thickness of 1.0-1.4 nm; 1.5 parts of polyethylene glycol methyl ether methacrylate are selected, with 47 repeating units in the polyethylene glycol segments; and 3 parts of 2-(dimethylamino)methacrylate are selected, with a purity ≥99%.
[0076] Preferably, the defoamer is selected from 0.4 parts of organosilicon quaternary ammonium salt; the leveling agent is selected from 0.8 parts of polydimethylsiloxane; the wetting agent is selected from 0.5 parts of polyoxyethylene ether; and the film-forming aid is selected from 7 parts of a 1:1 mixture of dodecyl alcohol ester and propylene glycol methyl ether.
[0077] Specifically, the thickener is 1.0 part of quaternary ammonium salt modified hydroxyethyl cellulose, with a modification degree of 0.45-0.55; the antifungal and bactericidal agent is 0.15 parts of a 1:2 mixture of 2-methyl-4-isothiazolin-3-one and 1,2-benzisothiazol-3(2H)-one; the filler is stearic acid modified ultrafine calcium carbonate (particle size 1.0 μm), nano zinc oxide (particle size 40 nm), and hollow glass microspheres (particle size 50 μm, density 0.23 g / cm³). 3 Mix 30 portions in a 3:1:1 weight ratio.
[0078] The preparation method includes the following steps:
[0079] First, modified nano-silica was prepared. The specific steps were as follows: 25 nm nano-silica was vacuum-dried at 105 °C for 4 h; a mixed solution of ethanol and water with a volume ratio of 8:2 was prepared; (3-glycidylpropoxy)trimethoxysilane was added to this mixed solution, and the pH was adjusted to 4.5 with glacial acetic acid. This pH value allows for a suitable hydrolysis rate of the silane coupling agent; pre-hydrolysis was carried out by stirring at room temperature for 30 min; the pretreated nano-silica was dispersed in ethanol and ultrasonically dispersed for 15 min; then, the pre-hydrolyzed silane coupling agent solution was slowly added dropwise at a rate of 2.5 mL / min, the temperature was raised to 60 °C, and the reaction was stirred for 4 h; finally, the mixture was separated by centrifugation at 8000 rpm, washed three times with ethanol, vacuum-dried at 60 °C for 12 h, and ground through a 200-mesh sieve.
[0080] Secondly, the water-based coating was prepared: acrylic emulsion and N-hydroxyethyl acrylamide were mixed at a stirring speed of 500 r / min; the prepared modified nano silica and graphene oxide were added and ultrasonically dispersed at 32℃ for 18 min; under nitrogen protection, polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)methacrylate ethyl ester were added sequentially, and the temperature was controlled at 48℃; thickener and filler were added sequentially, and the mixture was stirred for 3 min; finally, defoamer, film-forming aid and leveling agent were added dropwise at a rate of 0.8 g / min, and the mixture was stirred for another 35 min.
[0081] In this embodiment, by increasing the amount of N-hydroxyethylacrylamide and optimizing its mixing process with the emulsion, the crosslinking density of the coating was significantly enhanced. Simultaneously, the increased content of modified nano-silica, combined with the optimized surface modification process, further improved the mechanical strength and durability of the coating.
[0082] Example 3
[0083] A water-based coating suitable for cement floors and its preparation method
[0084] The water-based coating of this embodiment is formulated from the following components in parts by weight:
[0085] The acrylic emulsion is selected in 75 parts, which includes a pure acrylic emulsion and an aqueous acrylic emulsion mixed in a weight ratio of 4:1. The pure acrylic emulsion is a styrene-acrylic emulsion, and the aqueous acrylic emulsion is a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate.
[0086] Furthermore, 4.5 parts of N-hydroxyethyl acrylamide are selected, wherein the content of active double bonds is not less than 98%; 3.5 parts of modified nano silica are selected; 0.25 parts of graphene oxide are selected, with a sheet thickness of 1.2-1.6 nm; 1.8 parts of polyethylene glycol methyl ether methacrylate are selected, wherein the number of repeating units of polyethylene glycol segments is 48; and 3.5 parts of 2-(dimethylamino)methacrylate are selected.
[0087] Preferably, the defoamer is selected from 0.5 parts of organosilicon quaternary ammonium salt; the leveling agent is selected from 0.9 parts of polydimethylsiloxane; the wetting agent is selected from 0.5 parts of polyoxyethylene ether; and the film-forming aid is selected from 8 parts of a 1:1 mixture of dodecyl alcohol ester and propylene glycol methyl ether.
[0088] Specifically, the thickener is 1.2 parts of quaternary ammonium salt modified hydroxyethyl cellulose with a modification degree of 0.55-0.65; the antifungal and bactericidal agent is 0.18 parts of a 1:2 mixture of 2-methyl-4-isothiazolin-3-one and 1,2-benzisothiazol-3(2H)-one; the filler is stearic acid modified ultrafine calcium carbonate (particle size 1.1 μm), nano zinc oxide (particle size 45 nm), and hollow glass microspheres (particle size 55 μm, density 0.24 g / cm³). 3 Mix 35 portions in a 3:1:1 weight ratio.
[0089] The preparation method includes the following steps:
[0090] First, modified nano-silica was prepared. The specific steps were as follows: nano-silica with a particle size of 28 nm was vacuum dried at 105 °C for 4 h; a mixed solution of ethanol and water with a volume ratio of 8:2 was prepared; (3-glycidylpropoxy)trimethoxysilane was added to the mixed solution, and the pH was adjusted to 4.8 with glacial acetic acid; pre-hydrolyzed by stirring at room temperature for 30 min; the pretreated nano-silica was dispersed in ethanol and ultrasonically dispersed for 15 min; then the pre-hydrolyzed silane coupling agent solution was slowly added dropwise at a rate of 2.8 mL / min, the temperature was raised to 60 °C, and the reaction was stirred for 4 h; finally, the mixture was separated by centrifugation at 8000 rpm, washed three times with ethanol, vacuum dried at 60 °C for 12 h, and ground through a 200-mesh sieve.
[0091] Secondly, the water-based coating was prepared: acrylic emulsion and N-hydroxyethyl acrylamide were mixed at a stirring speed of 550 r / min; the prepared modified nano silica and graphene oxide were added and ultrasonically dispersed at 33℃ for 19 min; under nitrogen protection, polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)methacrylate ethyl ester were added sequentially, and the temperature was controlled at 48℃; thickener and filler were added sequentially, and the mixture was stirred for 3 min; finally, defoamer, film-forming aid and leveling agent were added dropwise at a rate of 0.9 g / min, and the mixture was stirred for another 38 min.
[0092] In this embodiment, by increasing the amount of functional components and optimizing their ratio, especially by increasing the content of film-forming aids, the film-forming performance and weather resistance of the coating were significantly improved. Simultaneously, the increased filler content and optimized particle size distribution provided better mechanical properties and surface finish.
[0093] Example 4
[0094] A water-based coating suitable for cement floors and its preparation method
[0095] The water-based coating of this embodiment is formulated from the following components in parts by weight:
[0096] The acrylic emulsion is selected in 80 parts, which includes pure acrylic emulsion and water-based acrylic emulsion mixed in a weight ratio of 4:1. The pure acrylic emulsion is a styrene-acrylic emulsion, and the water-based acrylic emulsion is a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate. The glass transition temperature of the random copolymer is 25-30℃.
[0097] Furthermore, 5 parts of N-hydroxyethyl acrylamide are selected, wherein the content of active double bonds is not less than 98%; 4 parts of modified nano-silica are selected; 0.3 parts of graphene oxide are selected, with a sheet thickness of 1.4-1.8 nm; 2 parts of polyethylene glycol methyl ether methacrylate are selected, wherein the number of repeating units of polyethylene glycol segments is 50; and 4 parts of 2-(dimethylamino)methacrylate are selected, with a purity ≥99%.
[0098] Preferably, the defoamer is selected from 0.6 parts of organosilicon quaternary ammonium salt; the leveling agent is selected from 1 part of polydimethylsiloxane; the wetting agent is selected from 0.6 parts of polyoxyethylene ether; and the film-forming aid is selected from 10 parts of a 1:1 mixture of dodecyl alcohol ester and propylene glycol methyl ether.
[0099] Specifically, the thickener is 1.5 parts of quaternary ammonium salt modified hydroxyethyl cellulose with a modification degree of 0.65-0.75; the antifungal and bactericidal agent is 0.2 parts of a 1:2 mixture of 2-methyl-4-isothiazolin-3-one and 1,2-benzisothiazol-3(2H)-one; the filler is stearic acid modified ultrafine calcium carbonate (particle size 1.2 μm), nano zinc oxide (particle size 50 nm), and hollow glass microspheres (particle size 60 μm, density 0.25 g / cm³). 3 Mix 40 portions in a 3:1:1 weight ratio.
[0100] The preparation method includes the following steps:
[0101] First, modified nano-silica was prepared. The specific steps were as follows: 30 nm nano-silica was vacuum dried at 105 °C for 4 h; a mixed solution of ethanol and water with a volume ratio of 8:2 was prepared; (3-glycidylpropoxy)trimethoxysilane was added to the mixed solution, and the pH was adjusted to 5.0 with glacial acetic acid; pre-hydrolyzed by stirring at room temperature for 30 min; the pretreated nano-silica was dispersed in ethanol and ultrasonically dispersed for 15 min; then the pre-hydrolyzed silane coupling agent solution was slowly added dropwise at a rate of 3.0 mL / min, the temperature was raised to 60 °C, and the reaction was stirred for 4 h; finally, the mixture was separated by centrifugation at 8000 rpm, washed three times with ethanol, vacuum dried at 60 °C for 12 h, and ground through a 200-mesh sieve.
[0102] Secondly, the water-based coating was prepared: acrylic emulsion and N-hydroxyethyl acrylamide were mixed at a stirring speed of 600 r / min; the prepared modified nano silica and graphene oxide were added and ultrasonically dispersed at 35℃ for 20 min; under nitrogen protection, polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)methacrylate ethyl ester were added sequentially, and the temperature was controlled at 50℃; thickener and filler were added sequentially, and the mixture was stirred for 3 min; finally, defoamer, film-forming aid and leveling agent were added dropwise at a rate of 1.0 g / min, and the mixture was stirred for another 40 min.
[0103] In this embodiment, by further increasing the content of each functional component and optimizing their ratio, a more complete synergistic network structure was formed in the coating system. In particular, the synergistic effect of the higher content of the pH-responsive component ethyl 2-(dimethylamino)methacrylate and the modified nano-silica formed a dynamic cross-linked network during the coating curing process, significantly improving the mechanical strength and durability of the coating. At the same time, the added filler system further optimized the overall performance of the coating through a multi-scale reinforcement effect. In addition, the increased amount and degree of modification of the thickener ensured that the system still had good stability and workability under high filler content conditions.
[0104] As can be seen from the above four embodiments, this invention achieves a synergistic effect among components by precisely controlling the proportions of each component and its preparation process. The optimized formula not only exhibits excellent workability but also outstanding durability and mechanical properties, providing a new technical solution for the application of cement floor coatings.
[0105] Comparative Example 1 (corresponding to Example 1)
[0106] A water-based coating suitable for cement floors and its preparation method
[0107] This comparative example uses a similar formulation to Example 1, but without the addition of N-hydroxyethyl acrylamide and modified nano-silica. The specific component ratios (by weight) are: 60 parts acrylic emulsion, 0.1 parts graphene oxide, 1 part polyethylene glycol methyl ether methacrylate, 2 parts ethyl 2-(dimethylamino)methacrylate, 0.2 parts defoamer, 0.5 parts leveling agent, 0.3 parts wetting agent, 4 parts film-forming aid, 0.5 parts thickener, 0.1 parts antifungal and bactericidal agent, and 20 parts filler. The specific selection of each component is the same as in Example 1.
[0108] The preparation method was basically the same as in Example 1, but the preparation step of modified nano-silica was omitted. The results showed that, due to the lack of the crosslinking network provided by N-hydroxyethylacrylamide and the reinforcing effect of modified nano-silica, the adhesion of the coating decreased significantly, the water resistance decreased by more than 50%, and obvious blistering occurred in repeated immersion tests.
[0109] Comparative Example 2 (corresponding to Example 2)
[0110] A water-based coating suitable for cement floors and its preparation method
[0111] This comparative example uses a similar formulation to Example 2, but replaces the nano-silica with an unmodified raw material. The amounts of each component in the formulation are the same as in Example 2, except that 3 parts of modified nano-silica are replaced with unmodified nano-silica.
[0112] The preparation process was the same as in Example 2, but the surface modification step of nano-silica was omitted. The results showed that due to the poor compatibility between nano-silica and the organic phase, obvious agglomeration occurred, resulting in a 30% reduction in the mechanical properties of the coating and an increase in surface roughness.
[0113] Comparative Example 3 (corresponding to Example 3)
[0114] A water-based coating suitable for cement floors and its preparation method
[0115] This comparative example uses a similar formulation to Example 3, but without the addition of ethyl 2-(dimethylamino)methacrylate. Other components and their amounts remain unchanged; the total formulation amount is supplemented by increasing the amount of acrylic emulsion.
[0116] The preparation process was the same as in Example 3, but the step of adding ethyl 2-(dimethylamino)methacrylate was omitted. The results showed that the lack of the pH-responsive component significantly deteriorated the rheological properties of the coating during application, and the stability of the cured coating decreased in alkaline environments, with a 40% reduction in durability.
[0117] Comparative Example 4 (corresponding to Example 4)
[0118] A water-based coating suitable for cement floors and its preparation method
[0119] This comparative example uses a similar formulation to Example 4, but the filler system is changed to 40 parts of a single calcium carbonate, thus eliminating the combined effect of nano zinc oxide and hollow glass microspheres.
[0120] The preparation process was the same as in Example 4, but the filler mixing steps were simplified. Results showed that, due to the lack of synergistic effects from the multi-stage fillers, the mechanical strength of the coating decreased by 45%, and the surface abrasion resistance significantly decreased.
[0121] Comparative Example 5 (corresponding to Example 1)
[0122] A water-based coating suitable for cement floors and its preparation method
[0123] In this comparative example, the thickener in Example 1 was replaced with ordinary hydroxyethyl cellulose (without quaternary ammonium salt modification), and the amount remained unchanged at 0.5 parts. All other components and amounts were the same as in Example 1.
[0124] The preparation process was the same as in Example 1. The results showed that using the unmodified thickener resulted in significant stratification of the coating during storage, poor leveling properties during application, and a significant reduction in the surface quality of the cured coating.
[0125] Comparative Example 6 (corresponding to Example 4)
[0126] A water-based coating suitable for cement floors and its preparation method
[0127] This comparative example uses a similar formulation to Example 4, but the film-forming aid is replaced with 10 parts of a single dodecyl alcohol ester, thus eliminating the synergistic effect of the two-component film-forming aid.
[0128] The preparation process was the same as in Example 4, but the mixing steps of the film-forming aids were simplified. Results showed that the minimum film-forming temperature of the coating increased, incomplete film formation occurred at low temperatures, and the coating's flexibility decreased by 25%.
[0129] The above comparative examples show that:
[0130] 1. The synergistic effect of N-hydroxyethyl acrylamide and modified nano-silica is crucial for improving coating adhesion and water resistance;
[0131] 2. Surface modification of nano-silica plays a decisive role in improving filler dispersibility and coating mechanical properties;
[0132] 3. The introduction of pH-responsive components significantly improved the coating's application performance and coating durability;
[0133] 4. The design of a multi-stage filler system plays an important role in improving the overall mechanical properties of the coating;
[0134] 5. Quaternary ammonium salt modification of thickeners has a significant impact on system stability and workability;
[0135] 6. The synergistic effect of two-component film-forming aids plays a key role in the film-forming performance and flexibility of the coating.
[0136] These comparative results fully demonstrate the necessity of the various innovative points of this invention and the significant technical effects.
[0137] Performance Testing and Evaluation
[0138] Based on the characteristics and application requirements of water-based coatings according to the present invention, the following test items were designed. All tests were conducted under standard environmental conditions (23±2℃, relative humidity 50±5%).
[0139] 1. Adhesion Test: The test method shall be in accordance with GB / T9286-1998. The sample shall be applied to a pretreated cement block and cured for 7 days. The adhesion shall then be tested using the cross-cut adhesion test. Simultaneously, the sample shall be immersed in water at 40℃ for 7 days, and the adhesion shall be tested again to evaluate water resistance.
[0140] 2. Crosslinking density test: The crosslinking density was determined using the gel content method. The cured coating sample was swollen with tetrahydrofuran for 24 hours, and the degree of swelling and gel content were measured. The crosslinking density was calculated using the Flory-Rehner equation.
[0141] 3. Nanoparticle Dispersion Analysis: The dispersion state of the modified nano-silica was observed using transmission electron microscopy (TEM). Ultrathin sections of the samples were negatively stained with phosphotungstic acid and observed under an accelerating voltage of 200 kV. Dynamic light scattering (DLS) was used to determine the particle size distribution of the dispersion system.
[0142] 4. Interface structure characterization: Scanning electron microscopy (SEM) was used to observe the cross-sectional morphology of the coating to evaluate the dispersion state of the filler and the interfacial bonding. The samples were subjected to liquid nitrogen embrittlement and observed under an accelerating voltage of 15 kV after gold sputtering.
[0143] 5. Dynamic Mechanical Properties Testing: The dynamic mechanical properties of the coating were tested using a Dynamic Mechanical Analyzer (DMA). Test conditions: heating rate 3℃ / min, frequency 1Hz, temperature range -50~150℃.
[0144] 6. Wear resistance test: conducted according to GB / T1768-2006, using a Taber abrasion tester, with a load of 1000g and a rotation speed of 60r / min, testing the mass loss after 1000 revolutions.
[0145] The test results are shown in the table below:
[0146] [Table 1] Test Results of Basic Coating Properties
[0147]
[0148] [Table 2] Results of Dynamic Mechanical Performance Tests
[0149]
[0150] The test results show that Example 4 exhibits the best overall performance, which is mainly due to the synergistic effect of the following aspects:
[0151] 1. Molecular-level synergistic mechanism: TEM observation revealed that the modified nano-silica exhibited a uniform dispersion in the matrix, with a particle size distribution ranging from 25 to 35 nm. DLS testing showed that the polydispersity index (PDI) of the dispersion system was below 0.2, indicating excellent dispersion uniformity. This favorable dispersion is attributed to the improved interfacial compatibility resulting from silane coupling agent modification, while the introduction of N-hydroxyethylacrylamide further enhanced the system's compatibility.
[0152] 2. Interface Enhancement Mechanism: SEM observation showed that the fracture surface of Example 4 exhibited typical ductile fracture characteristics, with a tight bond between the filler and the matrix interface and no obvious interface debonding phenomenon. This is mainly attributed to the chemical reaction between the epoxy groups on the surface of the modified nano-silica and the matrix, forming a chemically bonded interface layer. Simultaneously, the amphiphilic structure of polyethylene glycol methyl ether methacrylate forms an ordered arrangement at the interface, further optimizing the interface structure.
[0153] 3. Dynamic Crosslinking Network Formation Mechanism: DMA test results show that Example 4 has the widest glass transition range and the highest tanδ peak temperature, indicating that the system forms a network structure with different crosslinking densities. This network structure is formed due to the dynamic crosslinking effect of the pH-responsive components during film formation, ensuring that the coating has sufficient crosslinking density to guarantee mechanical properties while maintaining appropriate chain segment mobility to provide toughness.
[0154] The present invention has the following unexpected technical effects:
[0155] 1. Unexpected water resistance: Example 4 performed exceptionally well in the water resistance test, maintaining an adhesion level of 0 after immersion in water for 7 days, with no blistering or cracking. This far exceeded the expected performance indicators, which is attributed to a multi-barrier effect: the combined effect of the layered structure of the nanofiller, the dense structure of the dynamic cross-linked network, and interfacial chemical bonding.
[0156] 2. Excellent low-temperature flexibility: In the -20℃ impact test, the sample of Example 4 still maintained good flexibility, which is a performance that is difficult to achieve for water-based coating systems. This is mainly due to the multi-scale network structure formed by the system. The network of different scales provides different chain segment movement capabilities, ensuring toughness at low temperatures.
[0157] 3. Self-healing ability: During the wear resistance test, it was found that the surface of the sample in Example 4 was able to partially self-heal at room temperature after being slightly scratched. This phenomenon may be due to the dynamic reversible bonds formed on the surface by the pH-responsive component, and this discovery provides a new approach for the development of smart coating materials.
[0158] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.
Claims
1. A water-based coating suitable for cement floors, characterized in that, The water-based coating comprises the following components by weight: 60-80 parts acrylic emulsion, 3-5 parts N-hydroxyethyl acrylamide, 2-4 parts modified nano-silica, 0.1-0.3 parts graphene oxide, 1-2 parts polyethylene glycol methyl ether methacrylate, 2-4 parts ethyl 2-(dimethylamino)methacrylate, 0.2-0.6 parts defoamer, 0.5-1 part leveling agent, 0.3-0.6 parts wetting agent, 4-10 parts film-forming aid, 0.5-1.5 parts thickener, 0.1-0.2 parts mildew inhibitor and bactericide, and 20-40 parts filler; wherein the acrylic emulsion includes pure acrylic emulsion and water-based acrylic emulsion, and the weight proportions of the pure acrylic emulsion and water-based acrylic emulsion are... The ratio is 4:
1. The pure acrylic emulsion is a styrene-acrylic emulsion. The aqueous acrylic emulsion is selected from a random copolymer of methyl methacrylate, ethyl acrylate, and vinyl acetate. The modified nano silica is nano silica modified with (3-glycidoxy)trimethoxysilane, and the particle size of the nano silica is 20-30 nm. The thickness of the graphene oxide sheets is 0.8-1.8 nm. The number of repeating units of the polyethylene glycol segments in the polyethylene glycol methyl ether methacrylate is 45-50. The filler includes modified calcium carbonate, nano zinc oxide, and hollow glass microspheres, and the weight ratio of the modified calcium carbonate, nano zinc oxide, and hollow glass microspheres is 3:1:
1.
2. The water-based coating according to claim 1, characterized in that, The thickener is quaternary ammonium salt modified hydroxyethyl cellulose, and the antifungal and bactericidal agent comprises a mixture of 2-methyl-4-isothiazolin-3-one and 1,2-benzisothiazol-3(2H)-one in a weight ratio of 1:
2.
3. The water-based coating according to claim 1, characterized in that, The defoamer is an organosilicon quaternary ammonium salt, the leveling agent is polydimethylsiloxane, and the wetting agent is polyoxyethylene ether.
4. The water-based coating according to claim 1, characterized in that, The film-forming aid is selected from a mixture of dodecyl alcohol ester and propylene glycol methyl ether, wherein the weight ratio of dodecyl alcohol ester and propylene glycol methyl ether is 1:
1.
5. A method for preparing the water-based coating according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Preparation of modified nano-silica: Nano-silica was vacuum dried at 105℃ for 4 hours; Prepare an ethanol / water mixed solution, wherein the volume ratio of ethanol to water is 8:2; Add (3-glycidylpropoxy)trimethoxysilane to the mixture and adjust the pH to 4-5; Pre-hydrolysis was performed by stirring at room temperature for 30 minutes. The pretreated nano-silica was dispersed in ethanol and ultrasonically dispersed for 15 min. Slowly add the pre-hydrolyzed silane coupling agent solution, heat to 60℃, and stir the reaction for 4 hours; Centrifuge, wash three times with ethanol, vacuum dry at 60℃ for 12 hours, and grind through a 200-mesh sieve; (2) Preparation of water-based coatings: Mix the acrylic emulsion with N-hydroxyethylacrylamide at a stirring speed of 400-600 r / min; Add the modified nano-silica and graphene oxide obtained in step (1) and ultrasonically disperse for 15-20 min; Add polyethylene glycol methyl ether methacrylate and ethyl 2-(dimethylamino)methacrylate sequentially, and control the temperature at 45-50℃. Add the thickener and filler in sequence, and stir for 3 minutes; Add the defoamer, film-forming aid, and leveling agent dropwise at a rate of 0.5-1 g / min, and continue stirring for 30 min.
6. The method according to claim 5, characterized in that, In step (2), nitrogen protection is used when adding polyethylene glycol methyl ether methacrylate and ethyl 2-(dimethylamino)methacrylate.
7. The method according to claim 5, characterized in that, In step (2), when adding modified nano-silica and graphene oxide, the dispersion temperature is controlled at 30-35℃.
8. The water-based coating according to claim 1, characterized in that, The modified calcium carbonate is stearic acid-modified ultrafine calcium carbonate with a particle size of 0.7-1.2 μm; the nano zinc oxide has a particle size of 30-50 nm; and the hollow glass microspheres have a particle size of 40-60 μm and a density of 0.21-0.25 g / cm³.
Citation Information
Patent Citations
Graphene water-based super-wear-resisting floor paint and preparation method thereof
CN108059860A
Water-based inorganic floor coating and preparation method thereof
CN111253810A
Water-based resin, preparation method and application thereof, water-based paint and coating product
CN111393585A
Super-weather-resistant roof waterproof coating
CN118791896A